RISIKO CEDERA MATA PADA PEKERJA INDUSTRI PIPA BAJA - Bakara, Arnold Maruli; Ahyanti, Mei; Yushananta, Prayudhy (Poltekkes Kemenkes Tanjung Karang, 2020)
An eye injury is a trauma to the eye that can result in damage to the eyeball, eyelids, eye nerves and orbital cavity. Eye injuries can occur due to work processes in various industries, especially in the metal industry. PT. Bakrie Pipe Industry (BPI) is a metal industry that produces steel pipes by changing steel plate sheets into pipe shapes. One of the risks of work accidents in the production process is eye injury due to exposure to particles/gram of iron during the cutting process. This study aims to determine the risk factors for eye injury in workers in the Production Department of PT. Bakrie Pipe Industries, Bekasi, West Java.This study used a cross-sectional design involving all workers in the Production Department as research subjects, as many as 36 people. Data collection was carried out by interview and observation, then the data were analyzed using the chi-square test. The risk factors assessed were age, knowledge, attitude, noise and personal protective equipment against eye injury.The results showed that the risk factors for eye injury were knowledge (OR = 280.00; p value = 0,000), age (OR = 61.75; p value = 0,000), noise (OR = 39.00; p value = 0,000). , and the use of PPE (OR = 17.00; p value = 0.001).Increasing workers' knowledge about work risks is an effort that must be continuously carried out to avoid eye injuries, in addition to the necessity of using Personal Protective Equipment (PPE), and to carry out more intensive supervision.Â